Routine laboratory parameter dynamics and laboratory adverse events in psoriasis patients on long-term treatment with adalimumab, etanercept, and ustekinumab - Hoffmann, Jochen; Knoop, Christian; Enk, Alexander; Hadaschik, Eva (Acta dermato-venereologica, 2017)
Only limited data on laboratory parameter dynamics and safety under prolonged biologic treatment in a “real-world” scenario are available for recommendations on screening and monitoring. This study is a retrospective analysis of routine parameter dynamics and laboratory adverse events (LAE) in psoriasis patients on long-term treatment (n = 199) with tumour necrosis factor (TNF)-α-antagonists (adalimumab, etanercept), and the interleukin (IL)12/23-antagonist ustekinumab. Overall, neutrophil (PMN) counts (–11%) and triglycerides (+9%) changed considerably. TNF-α-antagonists and ustekinumab differentially affected lymphocyte counts (+13% and ±0%, respectively). Dynamics were pronounced during the first 180 days of treatment. In 340 treatment-years, 15 Common Terminology Criteria for Adverse Events (CTCAE) III–IV° LAE were recorded (11 involved liver enzymes). They prompted alteration of the biologic regime in only 2 cases. Age, sex, previous systemic treatments, and psoriatic arthritis did not significantly predict LAE. Liver enzyme and triglyceride screening may be warranted in some instances. Our data suggest that unguided monitoring of other routine laboratory parameters is unnecessary under long-term biologic treatment.
Gesehen am 18.10.2017
Epub ahead of print Feb 22, 2017